Análisis físico, químico y biológico de las aguas residuales en el punto de descarga del Río Cutuchi de la empresa envasadora congas ubicado en el cantón Salcedo, provincia de Cotopaxi, en el periodo 2015 - Tercero Caisalitin, Flavio Armando (2015)
The packaging industries liquefied petroleum gas, these are of vital importance in the Cotopaxi province, so with this activity generates jobs and economic progress to Ecuadorian families, so during packaging of LPG. It has produced pollutants to the cuases river by the use of water wich used for cylinder washing and maintenance of equipment, wich analysis was conducted in the discharge of Cutuchi river to development a treatment plant desing to the packaging CONGAS company throught laboratory results it was found that the parameters examined, as detergents, in laboratory analysis results is 1.08 and surpasses the permissible limits is 0.5 to 100 mg / L, BOD, In Laboratory analysis has as results 121 and passes the permissible limits that is 100 per 100mg0 / 2L, and therefore does not have current environmental regulations, Oils and Fats, in laboratory analysis has as results an….